Warming increases the sensitivity of seedling growth capacity to rainfall in six temperate deciduous tree species. Issue 1 (17th January 2018) - Rodgers, Vikki L; Smith, Nicholas G; Hoeppner, Susanne S; Dukes, Jeffrey S
Abstract : Using a fully factorial precipitation by warming experiment in an old-field ecosystem in the northeastern USA we studied the climatic sensitivity of seedlings of six native tree species. Warm and dry conditions suppressed seedling growth, but affected species differently by increasing mortality, enhancing rates of herbivory or decreasing foliar carbon uptake. Our results indicate that, in the northeastern USA, dry years in a future warmer environment could have damaging effects on the growth capacity of early secondary successional forests, through species-specific effects on leaf production, herbivory and mortality. Abstract: Predicting the effects of climate change on tree species and communities is critical for understanding the future state of our forested ecosystems. We used a fully factorial precipitation (three levels; ambient, −50 % ambient, +50 % ambient) by warming (four levels; up to +4 °C) experiment in an old-field ecosystem in the northeastern USA to study the climatic sensitivity of seedlings of six native tree species. We measured whole plant-level responses: survival, total leaf area (TLA), seedling insect herbivory damage, as well as leaf-level responses: specific leaf area (SLA), leaf-level water content (LWC), foliar nitrogen (N) concentration, foliar carbon (C) concentration and C:N ratio of each of these deciduous species in each treatment across a single growing season. We found that canopy warming dramatically increased the sensitivity of plant growth (measured as TLA) to rainfall across all species. Warm, dry conditions consistently reduced TLA and also reduced leaf C:N in four species ( Acer rubrum, Betula lenta, Prunus serotina, Ulmus americana ), primarily as a result of reduced foliar C, not increased foliar N. Interestingly, these conditions also harmed the other two species in different ways, increasing either mortality ( Populus grandidentata ) or herbivory ( Quercus rubra ). Specific leaf area and LWC varied across species, but did not show strong treatment responses. Our results indicate that, in the northeastern USA, dry years in a future warmer environment could have damaging effects on the growth capacity of these early secondary successional forests, through species-specific effects on leaf production (total leaves and leaf C), herbivory and mortality.